Malnutrition and Pneumonia among Under-five Children in Sadewa Maternal and Child Hospital, Yogyakarta, Indonesia - Myggi Rizdwike Nanda (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Pneumonia is one of the top causes of morbidity in children younger than 5 years old. In Indonesia, pneumonia was the second leading cause of death in children under five years in 2017. The most important risk factors for pneumonia in children are malnutrition, household air pollution, non-exclusive breastfeeding, low birth weight (2500 g), overcrowding (≥ 7 or more person in the same household), and lack of measles immunization. This study aimed to determine the relationship between nutritional status and pneumonia in under-five children in Sadewa Maternal and Child Hospital, Yogyakarta, Indonesia. Methods: Analytical observational studies with a cross-sectional approach. A total of 191 subjects took part in the study. Observations of the nutritional status and degree of pneumonia were carried out in this study. Univariate and bivariate data analysis was carried out with the help of SPSS version 25 software. Results: The majority of study subjects with pneumonia had normal nutritional status. Meanwhile, study subjects with severe pneumonia conditions had malnutrition nutritional status. The results showed that nutritional status was associated with pneumonia, with a p-value of < 0.05. Conclusion: There is a relationship between nutritional status and the severity level of pneumonia in children under five years old in Sadewa Maternal and Child Hospital, Yogyakarta, Indonesia.